The Counsellor’s Role in Educating the Emotionally Disturbed Child - Ofori, Kennedy Nyeseh (Current Research in Language, Literature and Education Vol. 2, 2021)
The notion that a child's behaviour may be more “disturbing” than disturbed has been of interest to educators of behaviourally deviant children. In this paper, a thorough appraisal of the emotionally disturbed child has been conceptualized variedly in the literature with various implications for school counsellors. The most important outcome of a guidance and counselling programme is a desirable change in students, such as improved study habits, better scholastic achievement, fewer scholastic failures, lower dropout rate and better home-school relations. The main objective of this paper was to unveil the various roles of the counsellor in providing education for the emotionally disturbed child. This discussion is particularly important because of the growing concern over the limited academic progress in special education children with emotional challenges. This, which has been largely attributed to inappropriate behaviours indicate poor social skills or poor general work habits exhibited by such children, thereby performing academically below their peers. Providing education to the emotionally disturbed child in the classroom, no doubt, will fall short of meeting the target without effective counselling. Suggestions on the roles counsellors should play to assist in the education of the emotionally disturbed child are made.